2021
DOI: 10.21203/rs.3.rs-315920/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fungal populations in the bedroom dust of children in Havana, Cuba, and its relationship with environmental conditions

Abstract: The study of the fungal community composition in house dust is useful to assess the cumulative exposure to fungi in indoor environments. The objective of this research was to characterize the fungal diversity of house dust and its association with the environmental conditions of bedrooms. For this, the dust was collected from 41 bedrooms of children between the ages of 8 and 9 with a family history of asthma, residents of Havana, Cuba. The fungal content of each sample was determined by two methods: plate cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The results the research performed by [46] determined that the volume of the room, relative humidity, and floor levels play an important role in fungal concentrations. Similarly, in another research performed by [53], indoor RH and indoor temperature exerted a positive relationship with specific spore genera as well as other dwelling characteristics such as the type of cleaning of the furniture, the presence of trees in front of the bedroom, the presence of air conditioning, and natural ventilation. A previous study on dwellings revealed positive associations between electrical heating and fungi [54].…”
Section: Figure 2 Study Design Resume Conclusionmentioning
confidence: 58%
“…The results the research performed by [46] determined that the volume of the room, relative humidity, and floor levels play an important role in fungal concentrations. Similarly, in another research performed by [53], indoor RH and indoor temperature exerted a positive relationship with specific spore genera as well as other dwelling characteristics such as the type of cleaning of the furniture, the presence of trees in front of the bedroom, the presence of air conditioning, and natural ventilation. A previous study on dwellings revealed positive associations between electrical heating and fungi [54].…”
Section: Figure 2 Study Design Resume Conclusionmentioning
confidence: 58%